2004
DOI: 10.1016/j.exphem.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Soluble c-kit receptor mobilizes hematopoietic stem cells to peripheral blood in mice

Abstract: These findings demonstrate that stem cells with long-term engraftment capabilities can be mobilized by s-kit, and that s-kit combined with G-CSF treatment leads to significant enhancement of engraftment efficiency, suggesting mobilization via disruption between c-kit and SCF as the mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 24 publications
3
43
0
1
Order By: Relevance
“…M uPAR also promotes adhesion of HSPCs to the BM microenvironment, as well as homing and engraftment of HSPCs, similar to α 4 β 1 and CXCR-4 (26,33,40,41). Our data also show that M uPAR is cleaved during mobilization of HSPCs, similar to cKit (42,43). We thus conclude that M uPAR is a receptor on HSPCs that regulates various processes of HSPCs in the BM.…”
Section: Discussionsupporting
confidence: 64%
“…M uPAR also promotes adhesion of HSPCs to the BM microenvironment, as well as homing and engraftment of HSPCs, similar to α 4 β 1 and CXCR-4 (26,33,40,41). Our data also show that M uPAR is cleaved during mobilization of HSPCs, similar to cKit (42,43). We thus conclude that M uPAR is a receptor on HSPCs that regulates various processes of HSPCs in the BM.…”
Section: Discussionsupporting
confidence: 64%
“…22 Moreover, disruption of c-kit signaling by the administration of soluble c-kit induces modest HPSC mobilization and also augments mobilization in response to G-CSF. 23 On the other hand, stimulation of c-kit signaling by administration of kitL induces robust HPSC mobilization 24 and c-kit-deficient mice have reduced G-CSF-induced mobilization. 25,26 In addition, mice deficient in the protease matrix metalloproteinase 9 (MMP-9), which is thought to mediate kitL cleavage, mobilize normally in most strains of mice.…”
Section: G-csf Mobilizes Hspcs Through a Hematopoietic Intermediatementioning
confidence: 99%
“…21,31,48 Data from a number of preclinical models showed that inhibition of these receptor-ligand interactions resulted in enhanced progenitor cell mobilization. [49][50][51] Although hematopoietic cells mobilized to peripheral blood for collection contain distinct populations of true stem cells and differentiated progenitor cells, they are often referred to collectively as stem cells. 52 In the BM and peripheral blood, stem cells are characterized by Ags specific to various lineages of hematopoietic cell differentiation.…”
Section: The Biology Of Stem Cell Mobilizationmentioning
confidence: 99%